2012
DOI: 10.1002/mabi.201290009
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Biosci. 3/2012

Abstract: Cover: The cover image shows thermo‐responsive polymer brushes with various chain lengths prepared by ATRP and retention of lymphocyte on them. The interaction between PIPAAm‐brush and lymphocyte was controlled by modulating the PIPAAm brush length and changing the temperature. Thus, PIPAAm brush grafted glass beads can be used as effective cell separation matrices. Further details can be found in the article by K. Nagase, N. Mukae, A. Kikuchi, and T. Okano* .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…In tissue engineering applications these coatings, which afford fully cohesive cell sheets of relatively large size, obviate as mentioned the digestion with enzymes (e.g., trypsin), which are known to harm and adversely affect cell–surface and cell–cell properties . This behavior has been exploited, as alluded to above, in cell–sheet engineering, which represents a scaffold‐free technology and has been successfully used in clinical applications, such as in the treatment of patients with disorders of the cornea or to capture lymphocytes for periodontal regeneration . The pioneering work of Okano and co‐workers in this area, who exploited PNIPAM brushes as a workhorse system, has been more recently expanded to included brushes of PNIPAM‐ co ‐poly(oligoethylene glycol) methacrylate (POEGMA), POEGMA‐ co ‐PDEGMA, poly(MEO 2 MA 50 ‐ co ‐HOEGMA 20 ‐ co ‐HEMA 30 ), poly(dimethylaminoethyl methacrylate), and poly[tri(ethylene glycol) ethyl ether methacrylate] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tissue engineering applications these coatings, which afford fully cohesive cell sheets of relatively large size, obviate as mentioned the digestion with enzymes (e.g., trypsin), which are known to harm and adversely affect cell–surface and cell–cell properties . This behavior has been exploited, as alluded to above, in cell–sheet engineering, which represents a scaffold‐free technology and has been successfully used in clinical applications, such as in the treatment of patients with disorders of the cornea or to capture lymphocytes for periodontal regeneration . The pioneering work of Okano and co‐workers in this area, who exploited PNIPAM brushes as a workhorse system, has been more recently expanded to included brushes of PNIPAM‐ co ‐poly(oligoethylene glycol) methacrylate (POEGMA), POEGMA‐ co ‐PDEGMA, poly(MEO 2 MA 50 ‐ co ‐HOEGMA 20 ‐ co ‐HEMA 30 ), poly(dimethylaminoethyl methacrylate), and poly[tri(ethylene glycol) ethyl ether methacrylate] …”
Section: Introductionmentioning
confidence: 99%
“…[1,21] This behavior has been exploited, as alluded to above, in cell-sheet engineering, which represents a scaffold-free technology and has been successfully used in clinical applications, such as in the treatment of patients with disorders of the cornea or to capture lymphocytes for periodontal regeneration. [22][23][24] The pioneering work of Okano and co-workers in this area, who exploited PNIPAM brushes as a workhorse system, has been more recently expanded to included brushes of PNIPAM-co-poly-(oligoethylene glycol) methacrylate (POEGMA), POEGMAco-PDEGMA, poly(MEO 2 MA 50 -co-HOEGMA 20 -co-HEMA 30 ), poly(dimethylaminoethyl methacrylate), and poly[tri-(ethylene glycol) ethyl ether methacrylate]. [1,[25][26][27][28] Homopolymer brushes that exhibit a lower critical solution temperature (LCST) in the vicinity of physiological temperatures are scarcer.…”
Section: Introductionmentioning
confidence: 99%
“…A lymphocyte subpopulation, i.e., B cells and T cells, was separated using PIPAAm-brush-modified glass beads packed in a column. 111 PIPAAm-brush-modified glass beads with various brush lengths were prepared, because previous reports indicated that the PIPAAm brush length determined the cell adhesion properties. 57,112 Lymphocyte retention at 37 1C decreased with increasing PIPAAm brush length, and the recovery rate at 5 1C increased, because the surface hydrophilicity increased with increasing PIPAAm brush length.…”
Section: Cell-separating Materials Based On Thermoresponsive Polymersmentioning
confidence: 99%
“…6 and S7 †). 50 The copolymer brush-modied glass beads exhibited larger cos q, determined by contact angle measurements as shown in Fig. 50 The copolymer brush-modied glass beads exhibited larger cos q, determined by contact angle measurements as shown in Fig.…”
Section: Thermoresponsive Wettability Change Of Copolymer Brushesmentioning
confidence: 90%
“…The amount of graed copolymer on the surface of the glass beads was determined by micro nitrogen analysis using a nitrogen microanalyzer (ND-100, Mitsubishi Chemical Analytech, Tokyo, Japan). The amount of graed copolymer on the glass beads was calculated by the following equation: 50 Grafted polymer ¼ % N P % N P ðcalcdÞ Â ð1 À % N P =% N P ðcalcdÞÞ Â S (4) where % N is the percent nitrogen increase determined by nitrogen microanalysis, % N(calcd) is the calculated theoretical weight percent of nitrogen in the copolymer, S is the specic surface area of the glass beads (the calculated data: 0.0104 m 2 g À1 ), and the subscript P denotes copolymer.…”
Section: Wettability Change Of Thermoresponsive Copolymer Brushesmentioning
confidence: 99%